The growth of Islamic banking and finance in Malaysia. - Kayadibi, Saim (Mazars Group, 2011)
Islamic banking and finance, is increasingly becoming a popular field of interest for economists and finance institutions for more than four decades, which has made a considerable niche area in the international financial markets. Islamic Banking and Finance currently provides services in more than seventy countries not only in Muslim countries but also in non-Muslim countries including Western, African and Asian countries. In terms of institutionalization, Malaysia is one of the most developed and fast growing country in the world in Islamic Banking and Finance services. Therefore this paper attempts to investigate, in general, the growth of Islamic Banking and Finance System in Malaysia through touching upon its fundamental roots how and with which instruments the system became successfully implemented that attracted the increasing global awareness.